The changing nature of spam 2.0 - Potdar, Vidyasagar; Firoozeh, N.; Ridzuan, Farida; Like, Y.; Mukhopadhyay, D.; Tejani, D. (ACM, 2012)
Spam 2.0 (or Web 2.0 Spam) is referred to as spam content that is hosted on Web 2.0 applications (blogs, forums, social networks etc.). Such spam differs from traditional spam as this is targeted at Web 2.0 applications and spreads through legitimate websites. The main problems with Spam 2.0 is spam websites get undeserved high ranking in search engines, damage the reputation of legitimate websites, wastes' valuable computing resources and deceives users resulting in proliferation of scam, fraud and other security attacks. Protecting the Internet against Spam 2.0 attacks is increasingly becoming important due to the potential threats it poses to the innocent web users. The paper contributes in this direction by attempting to understand the root cause of the problem, by investigating the changing nature of Spam 2.0. To understand this we setup an online discussion forum as a Honeypot to capture spam content. The collected data is analysed to identify trends within the spam corpus, which includes repetitiveness in the use of email addresses, patterns within email addresses, repetitiveness of forum posts, domains used for spamming, keywords and categories, origin of spam traffic. In the future we aim to use these trends in developing a preventive or early detection system that could predict future spam activities and would allow us to take pre-emptive actions to address them.